2018
DOI: 10.1007/s10120-018-0845-7
|View full text |Cite
|
Sign up to set email alerts
|

Early tumor shrinkage and depth of response in patients with advanced gastric cancer: a retrospective analysis of a randomized phase III study of first-line S-1 plus oxaliplatin vs. S-1 plus cisplatin

Abstract: In AGC patients receiving the first-line therapy, ETS and DpR might be predictors for PFS and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
(36 reference statements)
0
4
1
Order By: Relevance
“…The relationship between DpR and prognosis was analyzed. The results showed that DpR was correlated with PFS and OS ( 64 ), which was different from the results of Osumi et al ’s.…”
Section: Application Of Dpr In Gastric Cancercontrasting
confidence: 81%
“…The relationship between DpR and prognosis was analyzed. The results showed that DpR was correlated with PFS and OS ( 64 ), which was different from the results of Osumi et al ’s.…”
Section: Application Of Dpr In Gastric Cancercontrasting
confidence: 81%
“…S-1 is an oral fluoropyrimidine composed of 3 pharmacological compounds, including tegafur, gimeracil, and oteracil potassium, at a molar ratio of 1:0.4:1, and it has been widely used among Asian patients with advanced gastric cancer (aGC), breast cancer, and pancreatic carcinoma. [68] However, insufficient positive evidence has been obtained to establish its therapeutic value in patients with colorectal cancer. A large-scaled, open-label, non-inferiority, randomized, phase 3, multicentre trial (JCOG0910) explore the non-inferiority of S-1 compared with capecitabine as adjuvant treatment in patients with stage III colorectal cancer, and 3-year disease-free survival was 82.0% (95% confidence interval [CI]: 78.5–85.0) for the capecitabine group and 77.9% (95% CI: 74.1–81.1) for the S-1 group (hazard ratio [HR], 1.23, 99.05% CI: 0.89–1.70; 1-sided P non-inferiority = .46).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, we first selected chemotherapy with SOX plus bevacizumab to shrink both tumors and to control the micrometastases. SOX has been shown to be effective for gastric cancer [13,14], and SOX plus bevacizumab has been shown to be effective for metastatic colorectal cancer [15]. Therefore, we selected the SOX plus bevacizumab regimen for this patient.…”
Section: Discussionmentioning
confidence: 99%